2016
DOI: 10.18632/oncotarget.13501
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic silencing of mircoRNA-506-3p enhances COTL1 oncogene expression to foster non-small lung cancer progression

Abstract: Although previous studies suggested that microRNA-506-3p (miR-506-3p) was frequently downregulated, and functioned as a tumor suppressor in several cancers, the biological role and intrinsic regulatory mechanisms of miR-506-3p in non-small cell lung cancer (NSCLC) remain elusive. The present study found miR-506-3p expression was downregulated in advanced NSCLC tissues and cell lines. The expression of miR-506-3p in NSCLC was inversely correlated with larger tumor size, advanced TNM stage and lymph node metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…The results of the present study demonstrated a decrease in the miR-506-3p expression levels in PC-9GR cells, as compared with those in the parental cells. The cell proliferation assay demonstrated that miR-506-3p mimics inhibited the growth of both PC-9GR and PC-9 cells compared with miR-NC mimics, which is consistent with the findings of a previous study on the anti-proliferative function of miR-506-3p in NSCLC cells (22). Notably, the overexpression of miR-506-3p markedly increased the cell viability reduction and apoptosis following gefitinib treatment in PC-9GR cells, while the inhibition of miR-506-3p was demonstrated to have the opposing effect.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the present study demonstrated a decrease in the miR-506-3p expression levels in PC-9GR cells, as compared with those in the parental cells. The cell proliferation assay demonstrated that miR-506-3p mimics inhibited the growth of both PC-9GR and PC-9 cells compared with miR-NC mimics, which is consistent with the findings of a previous study on the anti-proliferative function of miR-506-3p in NSCLC cells (22). Notably, the overexpression of miR-506-3p markedly increased the cell viability reduction and apoptosis following gefitinib treatment in PC-9GR cells, while the inhibition of miR-506-3p was demonstrated to have the opposing effect.…”
Section: Discussionsupporting
confidence: 90%
“…Yin et al (21) reported that miR-506-3p was upregulated in lung cancer tissue in 83% of patients with lung cancer; however, the elevation in miR-506-3p expression inhibited tumor growth in lung cancer cells in vivo (17). Another recent study detected miR-506-3p downregulation in NSCLC and revealed that miR-506-3p inhibited NSCLC progression (22). In the present study, the downregulation of miR-506-3p expression in NSCLC was confirmed, and the role of miR-506-3p in mediating gefitinib sensitivity in NSCLC cells was identified.…”
Section: Discussionmentioning
confidence: 99%
“…Both UCA1 silencing and miR-143 overexpression could cause a significant decrease of mitogen-activated protein kinase 1 (MAPK1) [92]. Similarly, UCA1 contributed to proliferation and invasion of non-small cell lung cancer by functioning as a ceRNA to miR-506-3p, up-regulating its direct downstream target, coactosin-like protein 1 (COTL1) [93].…”
Section: Lung Cancermentioning
confidence: 99%
“…Has-miR-1270 was reported to interacted with circRNAs to regulate the tumorigenesis and development of LADC [40] and the cell invasion and migration in NSCLC [41]. Has-miR-506-3p was identi ed as a tumor suppressor in several cancers, including NSCLC [42] and colorectal cancer [43]. It can also reverse ge tinib resistance in NSCLC by targeting Yes-associated protein 1 [44].…”
Section: Discussionmentioning
confidence: 99%